1990
DOI: 10.1079/pns19900023
|View full text |Cite
|
Sign up to set email alerts
|

The sodium pump and other mechanisms of thermogenesis in selected tissues

Abstract: Whole-body heat production is a consequence of several biochemical events. Specific sites of heat production have been isolated, some being greater contributors to whole-body oxygen consumption than others. Tissues of the splanchnic bed (the gastrointestinal tract and liver) make up only 4 4 % of whole-body mass, but account for 40% of total ATP utilization. Skeletal muscle accounts for a much larger proportion of whole-body mass (50%), but accounts for only 20% of whole-body ATP use. Two major biochemical eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 87 publications
0
36
1
Order By: Relevance
“…The ATP demand of protein synthesis consumes 12-25% of total energy expenditure in mammalian muscle (Kelly and McBride, 1990;Rolfe and Brown, 1997). Reducing this energetically expensive cellular process can make an important contribution to global metabolic rate depression during hibernation and other states of hypometabolism (Frerichs et al, 1998;Storey, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The ATP demand of protein synthesis consumes 12-25% of total energy expenditure in mammalian muscle (Kelly and McBride, 1990;Rolfe and Brown, 1997). Reducing this energetically expensive cellular process can make an important contribution to global metabolic rate depression during hibernation and other states of hypometabolism (Frerichs et al, 1998;Storey, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of dynein and kinesin-dependent traffic for a single cargo ensures at least a proportion of oocyte mitochondria remain in the cytosol distinct from the spindle. This may be important for serving ATP supply at regions of high ATP demand such as the Na-K ATPase at the plasma membrane (Houghton et al, 2003;Kelly and McBride, 1990).…”
Section: (B-d)mentioning
confidence: 99%
“…Ferrell (1988) showed that in sheep, total viscera and nervous tissue account for 58.5% of oxygen consumption although they represent only 11% of body weight. This phenomenon is attributable to two major energy requiring processes occurring in the gut: activities of the Na + , K + -ATPase enzyme and protein turnover (Lobley 1988;Kelly and McBride 1989;McBride and Kelly 1990). Kelly et al (1993) estimated Na + , K + -ATPase enzyme and protein synthesis activities to account for 15.2-41.4% and 26.5-31% as a portion of visceral oxygen consumption, respectively.…”
Section: Ii3 Metabolic Cost Associated With Endogenous N Lossesmentioning
confidence: 99%